When Refutation and Deep Reasoning Questions Lose Their Edge: The Case of Short, Narrated Videos. (September 2022) - Schroeder, Noah L.; Siegle, Robert F.; Verma, Vipin; Craig, Scotty D.
Virtual humans are virtual characters within multimedia learning environments designed to aid the learning process. While there is a large variety of research examining how to design the physical appearance of the character or the teaching strategies it should embody, there is comparatively little work around the design of the narrative the virtual human uses to communicate with the learner. In this study, we examine the use of four different types of text structures to structure the character's narrative in an instructional video: expository, refutation text, deep reasoning questions, and refutation text and deep reasoning questions; and their effects on learning, perceptions, attitudes, and emotions about genetically modified foods. Our results largely indicated no significant differences between the different communication strategies. We hypothesize that the length, dosage, and pacing of the intervention could explain why we did not see benefits from the different narrative structures that have been found in other contexts.